2015
DOI: 10.1080/19415257.2015.1010015
|View full text |Cite
|
Sign up to set email alerts
|

Professional development seen as employment capital

Abstract: Practitioners need to invest in professional development to enhance credibility, job security and employment prospects. Employer expectations of continuing development as a performance measure link to the notion of career capital; namely that knowledge competence influences job advancement. This study uses an interpretivist approach to explore whether human resource practitioners see professional development as capital. The findings reveal that individuals appreciate the impact of development in confidence, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…The study's context A public context of harsh critics who denigrate the HR function as a quasi-profession (Gold et al 2013) justifies an investigation of working practitioner views. A literature emphasis on self-agency complements the investigation of a subjective, individual view of development (Mackay 2015). Roessger (2013, 17) argues researchers of CPD should conduct: 'Empirical designs in small-scale, controlled settings [...] to explore how social, affective and perceptional variables influence knowledge'.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study's context A public context of harsh critics who denigrate the HR function as a quasi-profession (Gold et al 2013) justifies an investigation of working practitioner views. A literature emphasis on self-agency complements the investigation of a subjective, individual view of development (Mackay 2015). Roessger (2013, 17) argues researchers of CPD should conduct: 'Empirical designs in small-scale, controlled settings [...] to explore how social, affective and perceptional variables influence knowledge'.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, CPD resembles an umbrella construct promoted as a universal 'good thing'; good for the individual, the organisation, and society. But broad interpretations mask the theoretical ambiguity of professional learning and divergent definitions create employment tensions (Trede, Macklin and Bridges 2012;Mackay 2015). Roessger (2013, 18) states CPD is widely interpreted as: 'professional performance, income generation, public relations strategy and learner self-actualisation'.…”
Section: Professional Developmentopen To Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…PD programs place a strong emphasis on improving teacher practices; they allow for teachers to understand their role, develop a sense of occupational identity and achieve clarity in terms of their practices. A study conducted by Mackay (2017) identified that PD programs have three main purposes within a professional environment: knowledge competence, social networking opportunities and enhanced self-worth value of teachers. Knowledge competence concerns enhancing the professional skills of teachers through upgrading their knowledge and skills in the classroom environment.…”
Section: Purpose Of Professional Development For Teachersmentioning
confidence: 99%
“…So, an evidence-base of competence provides an anchor to assert professional identity in context (Mackay, 2015a;Brown, 2014 there is a move to gather, measure and analyse data in order to improve overall performance of both HR and the organization, but also to demonstrate the value of the HR function.…”
Section: Evidence Of Professional Developmentmentioning
confidence: 99%